Integrated Central Transport Terminal - Haboc, John Row I (Manila : National University, 2000)
South station transport terminal, a terminal and retail development project of Filinvest alabang Inc. It is the metro manila's biggest inter-modal transport terminal.
Title page -- Dedication -- Chapter I. The research problem and settings -- Chapter II. Hypothesis -- Chapter III. Methodologies -- Chapter IV. Case study -- Chapter V. Analytical framework of design solution -- Chapter VI. review of related literature -- Chapter VII. References.
Includes bibliographical references.
Keywords: INTER-MODAL TERMINAL